Penentuan Pusat Pertumbuhan Ekonomi Dalam Pengembangan Wilayah Di Eks. Karesidenan Besuki - Nindya Aditia Putra; Badjuri Badjuri; Hanim Anifatul (UPT Penerbitan Universitas Jember, 2017)
Research conducted aims to: 1)the know which area the center of growth in ex besuki residency , 2)the know what the sectorhave a competitive advantage in each area , 3)the know the impact of a multiplier income of the sector have a competitiveadvantage in each area , 4) to know a growth center in hinterland areas. An analysis method that used a method of quantitativeanalysis by using secondary data obtained from the Statistic Indonesia and other institutions needed. The analysis is useanalysis scalogram, analysis of shift share classic, and gravitation analysis. The analysis showed Jember district emerged as agrowth center in the region of ex Besuki residency because it has the largest number of facilities .The agricultural sector intosectors which it has value Cij ( competitive advantage ) highest among the other sectors in the four districts in ex Besukiresidency. The multiplier income calculations showed the electricty, gas and clean water have a multiplier largest income inJember district, sector buildings in Banyuwangi district, the electricty, gas and clean water in Bondowoso district, the otherservice sector in Situbondo district. While calculation gravitation analysis showed of the economic growth centers have amagnet for the region of hinterlandnya because it has value Tij ( attractiveness ) that also.